METODE PEMECAHAN MASALAH INTEGER PROGRAMMING - Siti Maslikhah (At-Taqaddum, 2015)
Decision variables in the problem solving linear programs are often in the form of fractions. In some cases there are specific desires the solution in the form of an integer (integer). Integer solution is obtained by way of rounding does not warrant being in the area of fisibel. To obtain integer solutions, among others, by the method of Cutting Plane Algorithm or Branch and Bound. The advantages of the method of Cutting Plane Algorithm is quite effectively shorten the matter, while the advantages of the method of Branch and Bound the error level is to have a little but requires quite a long calculation.